Iron Status in Pregnant Women in Latvia: An Epidemiological, Cross-Sectional, Multicenter Study According to WHO and UK Criteria - Roberta Rezgale; Iveta Pudule; Vinita Cauce; Kristine Klaramunta Antila; Violeta Bule; Gunta Lazdane; Dace Rezeberga; Laila Meija (Medicina, 2022)
Background and Objectives: During pregnancy, iron deficiency anaemia is a common problem associated with health risks for both the mother and her foetus/infant. This study aimed to investigate the prevalence of iron deficiency, iron deficiency anaemia, and related dietary patterns in pregnant women in Latvia. Materials and Methods: This cross-sectional, multicentre study included pregnancy data from 974 women. The sample selection was based on the stratification principle (population of women of childbearing age in regions of Latvia). Maternal demographic details, anthropometric measurements, iron status, dietary patterns, and supplementation information were obtained from maternal files and during interviews held in eight outpatient departments of medical institutions and maternity departments. The prevalence was assessed. Chi-square tests and logistic regression were used to identify associations between iron deficiency and sociodemographic characteristics, dietary patterns, and iron supplement intake during pregnancy. The criterion used for the diagnosis of iron deficiency anaemia is a Hb level <110 g/L in the 1st and 3rd trimesters and <105 g/L during the 2nd trimester as recommended by the WHO. However, the UK guideline was used for borderline iron deficiency, which is an SF level <30 μg/L in all trimesters. Results: The observed prevalence of anaemia was 2.8% in the first trimester, 7.9% in the second trimester, and 27.0% in the third trimester. The prevalence of iron deficiency was 46.7% in the first trimester, 78.1% in the second trimester, and 91.7% in the third trimester. No associations with dietary patterns were found. Single women had 1.85 times the odds (95% CI 1.07 to 3.18) of being anaemic than married women. Conclusions: Iron deficiency affects a large proportion of pregnant women in Latvia in all trimesters, with iron deficiency anaemia affecting pregnant women in the third trimester. Monitoring and intervention should be performed in a timely and more targeted manner.